Strengthening Community Participation with Simpeldesa Sambirejo Application: A Review of Agile and Digital Governance Principles (Agile Governance and Innovation Measurement Journal, 2024)
This research aims to determine the process of community empowerment through the Simpeldesa Sambirejo application. This research brings similarities to the application of Agile Government and Digital Governance principles in the development and implementation of these applications. Apart from that, the implementation of the Simpeldesa Sambirejo application also applies Digital Governance principles which involve the use of digital technology to improve the efficiency and quality of public services. The use of this application has provided significant benefits in facilitating public access to information and public services, thereby increasing public participation in the decision-making process. However, before the application becomes Simpeldesa, an agile and digital government is needed so that it can make maximum use of technology. This is directly related to how Simpeldesa as a government tool can contribute to society in providing agile and digital services. Therefore, it would be interesting to do so.